Environmental impact of the paper industry - Iglesias León, Silvia (1998)
The first task of an Environmental Impact Assessment (EIA) study is to carry out an environmental diagnosis of the affected area or to be affected by a certain activity. This implies knowing the environmental components and their interactions, also characterizing the environmental situation from that area before the implementation of the project. In the present investigation of a company in the paper industry, the purpose is to determine the impact it produces on the environment, and above all to reach a mitigation plan by preparing proposals and its feasibility through cost / benefit analyzes. .